(untitled) - Primrose, S. B. (Oxford, 1989)
Modern biotechnology" is used to distinguish newer applications of biotechnology, such as genetic engineering and cell fusion from more conventional methods such as breeding, or fermentation...
Keywords: Biotechnology,Công nghệ sinh học